Lafazh Matsal dalam Al-Qur’an dan Aplikasinya dalam Ilmu Al-Wujûh Wa An-Nazhâir - Ayaturrahman (Ulumul Qur'an: Jurnal Kajian Ilmu Al-Qur'an dan Tafsir, 2022)
This arcticle discusses one branch of the Qur'anic science, namely the science of al-Wujûh wa an-Nazhâir, where the researcher conducts this research by presenting and clarifying the most important aspects related to it, such as aspects of its definition, language and terms and their origins. , the attention of the scholars in it, the most important sources and literature in this science, as well as discussing the relationships between the science of interpretation and the science of Arabic. This research is library research. The primary sources are taken from the Qur'an and its translations, the books of commentary and the books of al-Wujûh wa an-Nazhâir, while the secondary sources are dictionaries such as al-Mufradat fi Gharib Al-Qur'an, Al-Itqân Fi Ulûm Al-Qur'an, Burhan Fi Ulûmil Qur'an, Mu'jam Mufahrâs li al-Fâzhz Al-Qur'an al-Karîm, Lisân al-'Arabic, and also other dictionaries. Based on the results of the research that has been carried out, there are conclusions that have been obtained by the author, lafazh matsal in terms of the science of al-Wujûh wa an-Nazhâir has different meanings. Lafazh matsal in the Qur'an has four meanings, namely: the nature of likeness, life lessons, way of life and punishment, and all of these meanings can be seen from the siyâq or the context of the lafazh.